X-rays - Morrison, Rob (Queensland Braille Writing Association Brisbane, 1995)
"X-Rays" is an educational book designed for young readers that introduces the concept of X-rays and their uses in medicine and beyond. It explains how X-rays work, highlighting their ability to see inside objects, including the human body, without invasive procedures.